Humanização no acolhimento dos familiares de pacientes internados em Hospital Geral - Sousa, Sandra Maria Costa de (2014)
The National Policy for Humanization of Hospital Care was established in 2003, aiming to promote a culture of humane health care. The guidelines are expressed in the method of inclusion of users, workers in service management and in health practices. It employs devices, updating the guidelines through strategies designed to promote changes in patterns of care and management. The mail goal of the present study was to identify the needs of welcoming family members during the hospital stay, and as specific objectives, to develop a group to support the family of inpatients as a humanization strategy, analyzing the welcoming of family of patients and the National Humanization Policy. A qualitative action research approach, using a group process, was applied to a large general teaching hospital, reference in the state, located in Fortaleza, Ceará State. The study subjects were family members accompanying inpatients in clinics A and B of that hospital during the study period. Data were collected from May to July 2013 through individual interviews, creating a support group for family members of hospitalized patients, and collage technique. The study was conducted on the basis of ethical considerations to humans, recommended by the Resolution 466/2012, from the National Board of Health, and initiated after the approval by the Research Ethics Committee of the institution. To maintain the commitment to confidentiality of the Informed Consent, the subjects were coded with the letter F (family member) and the number by order of registration. Data were analyzed using content analysis of Bardin. The results are presented as follows: presentation of family members; analysis of the interviews; completion of the Family Support Group; assessment of the group as a strategy of welcoming, through collage and analysis of the welcome at the hospital and the Humanization Policy. Our results allowed the achievement of the proposed objectives, and it is expected that they can support health professionals, as well as the administration of the hospital, to increase the actions and measures in infrastructure, including the welcome and effective humanization in assisting the family during hospitalization, with interest in the feelings of the family when accompanying the relative; the difficulties in dealing with feelings; the needs and obstacles in the hospital as well as in the forms of assistance related to information and psychological support requested.